Accounting for the numberphobic : a survival guide for small business owners - Fotopulos, Dawn. (New York : AMACOM/American Management Association, 2015)
Demystifies the financial dashboard--net income statements, cash flow statements, and balance sheets.
Includes bibliographical references and index.
Keywords: Small business -- Management; Small business -- Accounting; Managerial accounting